Technical Efficiency of Ginger Production in Ilam District of Nepal: A Stochastic Production Frontier Approach - Dikshya Khatiwada; Pappu Yadav (Advances in Agriculture)
This study measured the level of technical efficiency among smallholder ginger growers and examined the determinants of inefficiency by employing the stochastic frontier production function. The paper used a simple random sampling technique to interview 100 ginger farmers in Ilam, a leading ginger-producing district in Nepal, with the help of a pretested interview schedule. The STATA.13 software was used to obtain both stochastic frontier estimates and the determinants of technical inefficiency. The results revealed that the average farm-level technical efficiency is 67.8% which shows the scope of increasing the technical efficiency by 32.2%. The coefficients of seed and farmyard manure were positive and showed significant relation to ginger output at a 1% and 5% level of significance, respectively. Education level, training, and membership in cooperatives had a negative and significant impact on technical inefficiency, whereas areas under ginger production had a positive impact on technical inefficiency. Hence, improving the technical knowledge of farmers through training on optimum input use complemented with motivation to join agriculture cooperatives and farmer’s associations may increase the technical efficiency of ginger growers in the study area.